Comfortable mobile offices: A literature review of the ergonomic aspects of mobile device use in transportation settings. - Kamp, I.; Van Veen, S. A. T.; Vink, P. (Work, 2015)
BACKGROUND: The use of mobile devices as an addition to or replacement of desktop computers for traditional office work results in more flexibility of workplaces. Consequently transportation time is used for office work and this asks for comfortable mobile offices. OBJECTIVE: The aim of this review is providing a framework of the relevant elements for comfortable mobile offices and defining needs for future research. METHODS: This literature review draws on 68 papers, theses, reviews and critiques. RESULTS: The framework is based on existing literature on traditional office ergonomics and comfort literature for different transportation modes like trains, buses, airplanes and cars. CONCLUSIONS: The main differences with traditional offices are the type of devices, dynamic versus static situation, the sole use of mobile devices and therefore the need for a good arm support to avoid an uncomfortable neck flexion, limited space, and the presence of strangers which influence the privacy perception. Important topics for future research are: the effect on the employee and the environment of the ability and demand of working anywhere, and the requirements for the physical aspects of mobile offices.